Expression Profile of Immunoglobulin G Glycosylation in Children With Epilepsy in Han Nationality - Li, Yuejin; Shi, Fengxue; Wang, Guanglei; Lv, Jian; Zhang, Haitao; Jin, Hao; Chen, Xueyu; Wang, Meng; Li, Peirui; Ji, Long (Frontiers in Molecular Neuroscience, 2022)
Abstract Background Epilepsy is a chronic brain disease that recurs during childhood, and more than half of adult epilepsy originates from childhood. Studies suggested that immunoglobulin G glycosylation are closely related to neurological diseases. Here we analyzed the characteristics of the immunoglobulin glycosylation profile of children with epilepsy. Methods Patients were recruited in Taian, Shandong Province from December 2019 to March 2020. Serum IgG glycome composition was analyzed by hydrophilic interaction liquid chromatography with ultra-high-performance liquid chromatography (HILIC-UPLC) approach. Results The proportion of fucosylated glycans in total IgG glycans was 93.72% in the epilepsy patients, which was significantly lower than that in the control group (94.94%). A lower level of total monogalactosylated and digalactosylated glycans were observed in the epilepsy patients group (30.76% and 40.14%) than that in the controls (36.17% and 42.69%). There was no significant difference between the two groups in bisected GlcNAc glycans and sialylated glycans. Conclusions. The decrease of core fucosylation and galactosylation may promote the inflammatory reaction of the body and participate in the occurrence of epilepsy in children.